A survey on power and load-aware multipath node-disjoint routing protocol for MANET - Kumar. S, Sathishkumar; G, Ravi (International Journal of Engineering and Technology, 2019)
In Mobile Ad-hoc Network (MANET), the most challenging task is communication through multipath routing. Generally, each node in the network may have limited power resources to communicate with the other nodes without any backbone structures. So, an unbalanced traffic allocation among nodes may cause power dissipation in overloaded nodes. Due to this, path failure has occurred that degrades the network lifetime and its performance. As a result, power and load-aware multipath routing protocols have been proposed to reduce the energy consumption and link failure in the network. Hence, a multipath routing scheme is the most crucial in MANET to transmit the data packets efficiently. This paper presents a detailed review of power and load-aware based multipath routing for MANET. Primarily, different power and load-aware multipath routing protocols designed by previous researchers for MANET are briefly studied. Then, a comparative analysis is conducted to understand the drawbacks in those protocols and suggest the new solution to improve the multipath routing in MANET with high network performance.Â Â Â